2021
DOI: 10.3389/fimmu.2021.664787
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Host Noncoding RNAs in Mycobacterium tuberculosis Infection

Abstract: Tuberculosis remains a major health problem. Mycobacterium tuberculosis, the causative agent of tuberculosis, can replicate and persist in host cells. Noncoding RNAs (ncRNAs) widely participate in various biological processes, including Mycobacterium tuberculosis infection, and play critical roles in gene regulation. In this review, we summarize the latest reports on ncRNAs (microRNAs, piRNAs, circRNAs and lncRNAs) that regulate the host response against Mycobacterium tuberculosis infection. In the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 118 publications
(147 reference statements)
0
9
0
Order By: Relevance
“…Tuberculosis (TB) is a global infectious disease caused by a latent infection of the Mycobacterium tuberculosis (MTB) that attacks the host's immune system in an attempt to activate the infection, a disease caused by the bacterium. According to the World Health Organization (WHO), approximately 1.5 million people died from TB in 2018 [ 1 ]. Despite the continuous advances in medical technology and the development of vaccines, the morbidity of TB has not been significantly improved, posing a serious threat to human life and health [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis (TB) is a global infectious disease caused by a latent infection of the Mycobacterium tuberculosis (MTB) that attacks the host's immune system in an attempt to activate the infection, a disease caused by the bacterium. According to the World Health Organization (WHO), approximately 1.5 million people died from TB in 2018 [ 1 ]. Despite the continuous advances in medical technology and the development of vaccines, the morbidity of TB has not been significantly improved, posing a serious threat to human life and health [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then we found that the expression of NEAT1 was down-regulated in BM cells of both BCG and rBCG-DisA immunized mice, but up-regulated significantly in the organs of rBCG-DisA immunized mice after M. tuberculosis challenge ( Figures 3C–E ). A growing body of research has revealed abnormally expressed lncRNAs in macrophages of TB patients ( 57 ). Thus, these lncRNAs that screened in this study may play roles in the regulation of the trained immunity, which should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Different expression patterns of lncRNAs are emerging as critical regulators to control the function of innate and adaptive immune cell types and initiate effective defense mechanisms in TB ( Figure 2 and Table 1 ; Chen Y. G. et al, 2017 ; Wei et al, 2021 ).…”
Section: The Role Of Long Non-coding Rnas In Anti-tuberculosis Immunitymentioning
confidence: 99%
“…In addition, tissue-specific and condition-specific expression patterns suggest that lncRNAs provide potential biomarkers ( Statello et al, 2021 ). Therefore, in-depth elucidation of the effect and mechanism of lncRNAs may develop clinical prospects for precise TB diagnosis and treatments ( Lyu et al, 2021 ; Wei et al, 2021 ). In this paper, we review the progress of lncRNA roles in Mtb infection from host immunity to biomarkers and discuss its potential in clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%